AGAMA SEBAGAI PENGALLAHAN MASYARAKAT: Telaah Kritis atas Teori Émile Durkheim tentang Agama - Marianta, Yohanes I Wayan (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2011)
In The Elementary Forms of Religious Life, Emile Durkheim sets forth a thought-provoking theory of religion. Drawing on his literature research on totemistic religions, notably those of the Aboriginal tribes of Central Australia, Durkheim argues that religion serves as the symbolic representation of society. The sacred is nothing but the representation of the collective power of the clan. Totemism is, thus, a deification of society. This theory does not lead Durkheim to discredit religion as merely a product of illusion, hallucination, failed science, linguistic confusion, and the like. Rather, he argues that the fact that religion has survived for centuries reveal that religion must have fulfilled certain societal need. The Elementary Forms of Religious Life seeks to demonstrate the integrative social function held by religion in traditional societies as the conscience collective that holds society together. This article is aimed at both highlighting the contribution of Durkheim's theory to the sociology of religion and showing the blindspots and weaknesses of his theory.